KONTRIBUSI ABDUL QADIR HASSAN TERHADAP HADIS DAN ILMU HADIS DI INDONESIA - Dita Rahmawati Illahi Dita Rahmawati Illahi (AL-ATSAR: Jurnal Ilmu Hadits, 2023)
The study of an intellectual figure, especially in the field of hadith studies, is important to find the roots and origins of a perspective. This article discusses Abdul Qadir Hassan who is a hadith scholar in Indonesia and his actions. He is active in fostering and growing the Islamic Unity organization by becoming the head of the Islamic Unity Islamic Boarding School in Bangil. In addition, he is also active as a member of the Hisbah Council and a member of Rabithah Alam Islami. It didn't stop there, Abdul Qadir contributed to authorship such as the book Knowledge of Musthalah Hadith, Answered Words, and as a filler in 50 percent of the rubric in Al-Muslimun, at which time he also served as chairman of the Al-Muslimun editorial team. The purpose of writing this article is to explain his contribution to the field of study of hadith, especially in Indonesia. The method used in this paper is content data analysis using literature research (library research). So it can be concluded that the contribution of Abdul Qadir Hassan was very influential in the spread and development of the transmission of hadith to date.